Figure della madre nella poesia del Duemila: Elisa Biagini, Rosaria Lo Russo, Alessandra Carnaroli (ENTHYMEMA, 2020)
This essay examines three poetical works published in the 21th Century and focused on the figures of the mother and on motherhood: L’ospite by Elisa Biagini, Io e Anne by Rosaria Lo Russo and Sespersa by Alessandra Carnaroli. My aim is to demonstrate that in all three of these works the journey through and the reinterpretation of the mother's world are simultaneously a premise and a prefiguration of the making of a new subjectivity and female authoriality in poetry.
Keywords: 21st century poetry; mother; relationship; female subjectivity; epos